Ancestral Connections: Re-Evaluating Concepts of Superimpositioning and Vandalism in Rock Art Studies - Motta Ana Paula; Hampson Jamie (Open Archaeology)
The aim of this article is to comprehend the significance of superimpositions as social practices and processes and to deconstruct how notions of superimpositions and vandalism have been used in rock art studies. Although attempts in the past have been made to determine why certain motifs were intentionally placed on top of other images, superimposition and vandalism/iconoclasm are often – and unhelpfully – used interchangeably in rock art literature. Interpretations have mostly lingered on the negative connotations of superimpositions, such as the “defacement” of previous motifs. Here, we argue that uncritically categorising certain practices as vandalism – often from the perspective of a Western knowledge system – has a negative influence on interpretations of traditional art systems. Instead, by recognising the active role that past depictions played – and, in some places, continue to play – within contemporary Indigenous communities, we hope to clarify and expand conceptualisations of superimpositions in rock art research. Our case study focusses on superimpositioning in the Kimberley region of Australia.